Molecular marker sequences of cattle Cooperia species identify Cooperia spatulata as a morphotype of Cooperia punctata. - Sabrina Ramünke; Fernando de Almeida Borges; Elke von Son-de Fernex; Georg von Samson-Himmelstjerna; Jürgen Krücken (PLoS ONE)
The genus Cooperia includes important parasites of ruminants and currently contains 34 accepted species. However, even for those species infecting livestock, there is a considerable lack of molecular information and many species are only identifiable using subtle morphological traits. The present study aimed to provide molecular data to allow diagnosis of Cooperia species infecting cattle. Partial sequences of two mitochondrial (cytochrome oxidase 2, 12S rRNA gene) and two nuclear genes (isotype 1 β tubulin gene including two introns, internal transcribed spacers (ITS) were obtained from morphologically identified specimens of Cooperia pectinata, Cooperia punctata and Cooperia spatulata as well as from larvae of pure Cooperia oncophora and C. punctata laboratory isolates. Pairwise identity of ITS-2 sequences was very high and it was the only region able to identify a specimen as Cooperia sp. However, the ITS-2 was unreliable for diagnosis at the species level. All other marker sequences could not unequivocally be allocated to the genus Cooperia but allowed clear species identification with the exception of the pair C. punctata/C. spatulata for which no significant differences were found for any marker sequence. Maximum-likelihood phylogenetic analyses of individual genes as well as a multi-locus analysis covering all four sequences confirmed that specimen identified as C. spatulata were randomly distributed throughout the C. punctata cluster and formed no group of their own. In contrast, the other Cooperia species formed clearly separated and statistically supported clusters. These data indicate that C. spatulata is most likely only a morphotype of C. punctata and the name should be considered a synonym. Combinations of nuclear and mitochondrial markers should be used to identify morphotypes or cryptic species to benefit from excellent barcoding properties of the latter but allowing proper phylogenetic analyses and controlling for lineage sorting that might occur for mitochondrial genotypes within a species.